Effect of dietary inclusion of guanidinoacetic acid on broiler performance - Borges, Kamilla M.; Mello, Heloisa H. de C.; Café, Marcos B.; Arnhold, Emmanuel; Xavier, Hyara P. F.; Oliveira, Helder F. de; Mascarenhas, Alessandra G. (Revista Colombiana de Ciencias Pecuarias, 2020)
Background: Creatine and its precursor, guanidinoacetic acid (GAA), decrease protein degradation, avoiding amino acid offset to gluconeogenesis. Objective: To evaluate the inclusion of GAA in the pre-initial diet (1 to 7 days) on performance, digestibility, and blood parameters of broilers from one to 21 days of age. Methods: 252 male broiler chickens aged one day were distributed in a completely randomized design with seven replicates and 12 animals per experimental unit. Treatments consisted of a basal diet, and the basal added with 0.10 and 0.20% GAA. Results: From days 1 to 7, a tendency on improved feed conversion (FC) was observed for broilers receiving 0.20% GAA (p<0.10). Between 7 and 14 days, FC improved, as well as a tendency was observed on improved weight gain in animals fed 0.20% GAA. Animals that received 0.20% GAA showed higher blood concentrations of creatine kinase. Blood creatine and blood glucose did not differ between treatments at day six. The assimilation coefficient of crude protein increased during days 3 to 7 for animals receiving 0.20% GAA. On the period between 17 and 21 days, no difference was observed between treatments. Intestinal weight and length did not show significant differences. Conclusion: Dietary inclusion of 0.20% GAA during the pre-initial stage could improve weight gain and feed conversion of broilers between 1 and 14 days of age.